Beta‐blocker use is an independent risk factor for thunderstorm asthma. (18th March 2019) - Sultana, Ron V; McKenzie, Dean P; Fahey, Michael T; Sutherland, Michael; Nimorakiotakis, Vasilios
Abstract: Objective: To identify risk factors for thunderstorm asthma (TA) in subjects ≥15 years of age from information available in routine clinical records. Methods: Retrospective and hospital‐based case–control study of various clinical factors in all TA cases ( n = 53) who presented to a single‐site ED in November 2016 (TA16) and in a control group of patients ( n = 156) who presented to the same ED with asthma during the pollen season over eight non‐TA years. Bivariate analysis and multivariable logistic regression modelling was performed to calculate the odds of TA asthma in the presence of potential risk factors. Results: A logistic regression model revealed that the odds of TA were lower for age (odds ratio [OR] 0.97, 95% confidence interval [CI] 0.95–0.99), higher for Asian country of birth (OR 4.09, 95% CI 1.40–11.95) and higher for oral beta‐blocker use (OR 6.43, 95% CI 1.58–26.33) compared to controls. No difference was found between TA16 cases and controls for allergies (to medication, grass pollen, animal), hayfever, smoking, oral non‐steroidal anti‐inflammatory drugs, or aspirin. Newly diagnosed asthma was higher in TA16 cases versus controls (32.1% vs 12.2%, P = 0.001). Conclusions: Oral beta‐blocker medications, younger age and Asian‐born heritage are risk factors for TA. Further study is required to explore the potential association between beta‐blockers and TA.